Visualization of spatial conductivity irregularities within conductive rubber sheets. Issue 4 (4th July 2016) - Wernick, Helmut; Hoelzl, Patrick; Zagar, Bernhard G.
Abstract : Purpose: – The purpose of this paper is to present a fast and contactless measurement method to determine the spatial conductivity distribution within an intrinsically conducting polymer, more precisely a conductive rubber sheet specimen. As a consequence of the manufacturing process and the material composition, the conductivity distribution within the sheet is assumed to be inhomogeneous. Design/methodology/approach: – The current density distribution within the conductive rubber sheet due to an excitation current is estimated from the measured magnetic field distribution. Therefore, a GMR sensor is used to spatially sample the magnetic field above the specimen. Based on the estimated current density distribution and alternatively the local power dissipation calculated from a thermal image, the conductivity distribution within the specimen is determined. For comparison a reference measurement with a classical resistivity probe is done. Findings: – The measurement results show a good agreement between the developed and the classical method. Moreover, the developed measurement method requires less time and still offers a higher spatial resolution. Originality/value: – The presented results demonstrate the potential of the developed measurement method for determining the conductivity distribution within thin and planar specimens. Furthermore, conclusions can be drawn about the material homogeneity of the used test specimen.